SEKOLAH DASAR ALAM INKLUSIF BANJARBARU - Darajat, Tuhfatul; Sa'ud, Mohammad Ibnu (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Nature school is an alternative environment-based education that is currently developing in Indonesia. Natural schools are schools that use the school's natural environment as an arena for learning and interacting with the community. This helps students develop into human beings with character. Humans who are not only able to take advantage of nature, but also able to love and care for nature. Natural schools have a big vision and mission in supporting educational equity. The existence of inclusive education is one effort that is able to provide rights to children who tend to be less able in terms of many things such as economic or physical limitations. Inclusion is a government program that has a big goal of equalizing education for all people, inclusion is a program that unites all children, including children with disabilities, in one school. Natural schools are considered to be more effective as a basis for inclusive programs because of the principles of natural schools that liberate all curiosity and interest in learning. Natural schools use nature as the main medium for real and direct learning, this is also what is expected to trigger a sense of independence in children with disabilities because the nature does not provide convenience just like that and also provides a calming effect on children and provides a pleasant atmosphere when learning and playing in same time. Persons with disabilities are the main goal of the inclusion program, the high dropout rate has forced the government to make new policies related to education. Feelings of insecurity are the biggest cause for children with disabilities preferring to drop out of school. This problem continues to this day, so educational facilities that are comfortable for them must be put forward immediately for the sake of better equality of national education and intelligence.